Synthesis, nitric oxide release, and dipeptidyl peptidase-4 inhibition of sitagliptin derivatives as new multifunctional antidiabetic agents. Issue 23 (15th December 2018) - Xie, Yundong; Shao, Lihua; Wang, Qiutang; Bai, Yue; Chen, Zizhang; Li, Na; Xu, Yanhong; Li, Yiping; Yang, Guangde; Bian, Xiaoli
Graphical abstract: Highlights: All of the target compounds demonstrated excellent DPP-4 inhibitory properties and hypoglycemic activity. T1 -T4 exhibited NO releasing abilities, anti-platelet aggregation and ameliorating oxidative stress. Research indicated that compoundsT1 -T4 possessed amelioration of endothelial dysfunction. Abstract: Nitric oxide (NO) dysfunction has been found to be an important factor in both the development and progression of diabetic complications due to its many roles in the vascular system. Multifunctional compounds with hypoglycemic and endothelial protective action will be promising agents for the treatment of diabetes and its complications. In this study, a series of novel NO-donating sitagliptin derivatives and relevant metabolites were synthesized and evaluated as potential multifunctional hypoglycemic agents. All of synthetic compounds shown remarkable inhibitory activity against dipeptidyl peptidase IV (DPP-IV) in vitro and demonstrated excellent hypoglycemic activities in diabetic mice, similar to the activity of sitagliptin, and compoundsT1 -T4 shown different extents of NO-releasing abilities and potent antioxidant abilities in vivo . By screening in DPP-4, compoundT4 was recognized as a potent DPP-4 inhibitor with the IC50 value of 0.060 μM. Docking study revealed compoundT4 has a favorable binding mode. Furthermore, compoundsT1 -T4 exhibited different extents of NO-releasing abilities and excellent anti-platelet aggregation in vitro . The overall results suggested thatT4 could help to the amelioration of endothelial dysfunction by reducing blood glucose, lessening oxidative stress and raising NO levels as well as inhibiting platelet aggregation. Based on this research, compoundT4 deserves further investigation as potential new multifunctional anti-diabetic agent with antioxidant, anti-platelet aggregation and endothelial protective properties.